Liberia : Staff Report for the 2001 Article IV Consultation and Overdue Financial Obligations to the Fund-Review Following Declaration of Ineligibility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper examines Liberia's 2001 Article IV Consultation and Overdue Financial Obligations to the IMF. Liberia's policy performance, as well as its relations with donors and creditors, has deteriorated since the conclusion of the last Article IV Consultation and the last post-ineligibility review. Payments to the IMF have become increasingly irregular, although relations with the World Bank remain in hiatus. IMF staff proposes that the Executive Board note the intention to initiate the procedure on the suspension of Liberia's voting and related rights in the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet